Literature Review : Family Formation and Fertility as Risk-Coping Mechanisms - Cáceres-Delpiano, Julio (World Bank, Washington, DC, 2013)
This report reviews the role of family as an institution that helps individuals manage risk, specifically, how family formation and fertility impact risk management, by (1) presenting the literature on family formation and risk management, (2) reviewing the role of fertility, and (3) reviewing policy implications. Both family formation and fertility determine the size of the family network and, therefore, the gains from pooling risk within this network, while changes in the risk environment alter the gains from network size, which in turn influences family arrangements and fertility. The mechanisms available to cope with risk, along with the magnitude and the consequences of risk, vary widely with level of development, and as more individuals become involved in managing risk, the cost of these strategies should fall. Understanding the determinants of family formation and fertility thus remains critical to understanding how effectively households in the developing world are able to cope with risk.